Urine N-acetyl-Ser-Asp-Lys-Pro measurement as a versatile biomarker to assess adherence to angiotensin-converting enzyme inhibitors. Issue 2 (9th September 2021) - Kably, Benjamin; Billaud, Eliane M.; Derobertmasure, Audrey; Blanchard, Anne; Boutouyrie, Pierre; Azizi, Michel
Abstract : Background: Poor adherence to treatment is a major health issue in hypertension. The large number of drugs to be detected limits the implementation of chemical adherence testing by liquid chromatography/mass spectrometry (LC-MS/MS). AcSDKP, a peptide accumulating in the presence of angiotensin-converting-enzyme inhibitor (ACEI) treatment, has been validated as a proven marker of adherence by enzyme-linked immunosorbent assay. Our aim was to validate urine measurements of AcSDKP compared with active metabolites of various ACEI, measured simultaneously by LC-MS/MS. Method: We first studied the time-dependent relationships between urinary perindoprilat and AcSDKP in a pharmacokinetic/pharmacodynamic study in healthy volunteers. We then compared the sensitivity and specificity of urinary AcSDKP vs. three ACEI active metabolites (enalaprilat, perindoprilat, ramiprilat) taken as reference to detect nonadherence in spot urine samples from a prospective cohort of hypertensive outpatients. Results: The urinary excretion profiles of AcSDKP and perindoprilat were similar, exhibited a significant correlation, and showed excellent agreement in healthy volunteers. In patients, we found a similar agreement between AcSDKP and the three ACEI metabolites urinary concentrations. The sensitivity and specificity for adherence assessment of urine AcSDKP was 92.2 and 100%, respectively. We observed a difference in the evaluation of good adherence between ACEI metabolites (85.7%) and AcSDKP (79.0%) because of discrepancies in samples where AcSDKP reached undetectability quicker than ACEI metabolites. This characteristic of AcSDKP is of particular interest and could better reflect the true adherence status of patients. Conclusion: Overall, spot urine AcSDKP measurement by LC-MS/MS is a reliable marker of the intake of ACEI treatment and could substitute ACEI metabolites detection.